Analisis Produktifitas Menggunakan Metode ObjectiveMatrix (OMAX) (Studi Kasus: PT. Moradon Berlian Sakti) - Prima Fithri; Indra Firdaus (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2014)
PT. Moradon Berlian Sakti is Die Casting manufacturer of Honda motorcycle spare parts and other types of products, such as chair. Along with the rapid advancement of technology, PT. Moradon Berlian Sakti always strive to maintain and improve its existence. One of important factor that need to be noticed is the productivity issue. Productivity assessment can be conducted based on the comparison of company input and output in terms of materials, capital, labor and energy. After learning the level or productivity index, company leader can identify which condition has productivity shrinkage and make decision to increase productivity company based on those condition. Based on the calculations, the levels of productivity index in 2012, was virtually uniform from January to December. But in October the productivity is high and reach the level 94.33%. That is because that performance indicators are in accordance with expectation of company leader. While in December productivity dramatically decreased to 4.67%, it is because less supervision and control from the company.